IMPROVEMENT OF PHYSICAL FITNESS THROUGH CHEERFUL COLOURS CIRCUIT GAME - SUSANTI, RIKZA AZHARONA (JPUD - Jurnal Pendidikan Usia Dini, 2014)
Abstract: This research aims to find out how the process ofincreasing the physical fitness and the improvement of the physical fitness of grade B Kindergarten students throught cheerful colours circuit game. The research was carried out in Gardini kindergarten in East Jakarta from January to March2014. The research used action research method according to action research model of Kemmis dan Mc. Taggart made through two cycle consisting of 7 sessions in the first cycle and 4 sessions in the second cycle. The cycle consists of four steps: a) plannin; b) action (acting); c) observation (observing; and d) reflection (reflecting). The subjects were grade B in Gardini Kindergarten in East Jakarta consisting of 10 childern. The data was collected by the research instrument which refers to the dimensions of physical fitness. The end result of this study showed an increase in physical fitness of childern that is evidenced by the acquisition of classical physical fitness scores pre-action reaching 52.28%. After the first cycle had increased, the score reached 87.19% and the second cycle was obtained satisfactory classical scores reached 94.74%. Keywords: physical fitness, game, cheerful colours circuit game. Abstrak: Tujuan penelitian adalah untuk mengetahui proses permainan sirkuit warna-warni ceria dan peningkatan kebugaran jasmani anak melalui permainan sirkuit. Penelitian ini dilaksanakan di TK B Gardini Jakarta Timur, dimulai dari bulan Januari sampai dengan bulan Maret 2014. Penelitian tindakan (action research) ini menggunakan metode Kemmis dan Mc Taggart, melalui dua siklus yang tediri dari tujuh pertemuan pada siklus I dan empat pertemuan pada siklus II yang meliputi tahap perencanaan, tindakan, observasi dan refleksi. Subyek penelitian adalah 10 anak TK B Gardini Jakarta Timur yang berusia 5-6 tahun. Analisis data menggunakan analisis kuantitatif dan kualitatif (mix methods). Data kuantitatif dianalisis dengan menggunakan analisis deskriptif (tabel frekuensi, rata-rata, persentase, sntadar deviasi) sedangkan data kualitatif dianalisis dengan langkah reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi data. Data diperoleh dengan berpedoman pada instrumen penelitian yang mengacu pada dimensi kebugaran jasmani. Hasil penelitian ini menunjukkan adanya peningkatan kebugaran jasmani anak yang dibuktikan pada perolehan skor klasikal kebugaran jasmani pra-tindakan mencapai 52,28%. Penelitian dianggap berhasil setelah dilakukan tindakan. Pada siklus I mengalami peningkatan skor klasikal mencapai 87,19% dan pada siklus II diperoleh skor klasikal yang memuaskan mencapai 94,74%. Kata kunci: kebugaran jasmani, permainan, sirkuit warna-warni ceria